ANTIMICROBIAL AND ANTIOXIDATIVE ACTIVITY OF VARIOUS LEAF EXTRACTS OF AMPHORICARPOS VIS. (ASTERACEAE) TAXA - Gavrilović, Milan; Soković, Marina D.; Stanković, Milan; Marin, Petar D.; Dajić Stevanović, Zora; Janaćković, Peđa (Archives of Biological Sciences, 2016)
The antimicrobial and antioxidative activities of diethyl ether, 80% methanol and 50% acetone extracts of the leaves of three Amphoricarpos taxa: A. neumayerianus, A. autariatus ssp. autariatus and A. autariatus ssp. bertisceus (Asteraceae) from the Balkan Peninsula were investigated. The antimicrobial activity was determined by the broth microdilution assay against eight bacterial and eight fungal species. The in vitro antioxidative activity was assessed by the DPPH assay. The total phenolic and flavonoid contents were also determined. The most sensitive bacterial species were Bacillus cereus and Staphylococcus aureus. The best antibacterial potential was obtained for the methanol extract of A. neumayerianus, while the diethyl ether extract of this species showed the lowest effect. In general, the tested extracts showed higher activity than the commercial antibiotics streptomycin and ampicillin. Also, all micromycetes were sensitive to the tested extracts. The most sensitive was Trichoderma viride. The highest and lowest antifungal effect was determined in A. a. ssp. autariatus for the diethyl ether and acetone extracts, respectively. The highest total phenolic and flavonoid contents were determined in the methanol extract of A. a. autariatus. The best antioxidative activity was shown by the methanol extract of A. a. ssp. autariatus as comparing to matching extracts from the other two taxa. DOI: 10.2298/ABS160112068G Key words: Amphoricarpos; Asteraceae; leaf extracts; antimicrobial activity; antioxidative potential Received: January 12, 2016; Revised: February 9, 2016; Accepted: February 9, 2016; Published online: August 2, 2016 How to cite this article: Gavrilović M, Soković MD, Stanković M, Marin P D., Dajić-Stevanović Z, Janaćković P. Antimicrobial and antioxidative activity of various leaf extracts of Amphoricarpos vis. (Asteraceae) taxa. Arch Biol Sci. 2016;68(4):803-10.